Caracterização anatômica de espécies do gênero Ocotea Aubl. (Lauraceae) - Queiros, Gustavo Gomes de (Universidade Estadual Paulista (Unesp), 2022)
Ocotea Aubl. is one of the largest genera of Lauraceae, with about 400 species in tropical and subtropical regions. The genus, in its current circumscription, comprises 29 informal groups, of which the Ocotea pulchella group stands out, formed by five species with a sympatric distribution and most of them endemic to Brazil. The genus is polyphyletic and needs revision. The aim of this study was to characterize the leaf anatomy, epidermis and venation pattern of O. pulchella and O. tristis, both species of the Ocotea pulchella group, with phylogenetic proximity, seeking contributions to the taxonomy of species and the group. The leaf anatomical study, the characters of the epidermis and the venation pattern were performed from herbarium material of 29 specimens of O. pulchella and seven of O. tristis; at least two fully expanded leaves of each specimen were sampled and rehydrated until the complete expansion of the tissues and subsequently fixed. For leaf anatomy, cross sections of the median third of the petiole and leaf blade (including the edge and midbrid region) were performed, through freehand or from material included in historresin, which were stained according to the unusual techniques. Samples of the median part of the leaf blade (i.e. between the edge and the midbrid) were processed by epidermis dissociation techniques, for leaf epidermis analysis, and diaphanization of the leaf blade, for venation pattern analysis, and stained following the usual methodology. The anatomical analysis was performed by light microscopy through permanent slides mounted on synthetic resin. Eighty characters were analyzed for leaf anatomy, 8 characters for leaf epidermis and 4 for venation pattern for both species. The leaves are dorsiventral, hypostomatic, with the presence of secretory cells dispersed in the mesophyll, vascular bundles surrounded whole or partially by sclerenchymatic sheath in the leaf blade, midbrid and petiole, and commonly with trichomes on both surfaces. They have epidermal anticlinal cell wall in front view is curved to straight on both surfaces and eventually undulate on the abaxial side. Imperfect areolae were frequent and dendritic veinlets occur for most specimens. The variations of these characters occurred between the species, among the specimens and in the same sample, being frequently found in other species of the family. The taxonomic importance of leaf data needs to be corroborated by further studies including other species of the Ocotea pulchella group and other species of the genus. These results highlight the importance of analyzing a broad leaf sampling in studies that assess relevant characteristics for specific or interspecific taxonomic delimitation.

Ocotea Aubl. é um dos maiores gêneros de Lauraceae, com cerca de 400 espécies nas regiões tropicais e subtropicais. O gênero, em sua circunscrição atual, compreende 29 grupos informais, dos quais, destaca-se o Grupo Ocotea pulchella, formado por cinco espécies com distribuição simpátrica e de maioria endêmica do Brasil. O gênero é polifilético e necessita de revisão. O objetivo desse estudo foi caracterizar a anatomia, epiderme e padrão de venação foliar de O. pulchella e O. tristis, ambas espécies do Grupo Ocotea pulchella, com proximidade filogenética, buscando contribuições para a taxonomia das espécies e do grupo. O estudo anatômico foliar, os caracteres da epiderme e do padrão de venação foram realizados a partir de material herborizado de 29 espécimes de O. pulchella e sete de O. tristis; foram amostradas, pelo menos, duas folhas plenamente expandidas de cada espécime que foram reidratadas até a completa expansão dos tecidos e, posteriormente, fixadas. Para a anatomia foliar, foram realizadas seções transversais do terço mediano do pecíolo e da lâmina foliar (incluindo a região da nervura central e do bordo), a mão livre ou a partir de material incluído em historresina, que foram coradas segundo técnicas usuais. Amostras da porção mediana da lâmina foliar (i.e, entre o bordo e a nervura central) foram processadas pelas técnicas de dissociação da epiderme, para análise da epiderme foliar, e diafanização da lâmina foliar, para análise do padrão de venação, e coradas seguindo metodologia usual. A análise anatômica foi realizada em microscopia de luz através de lâminas permanentes montadas em resina sintética. Foram analisados 80 caracteres para a anatomia foliar, 8 caracteres para a epiderme foliar e 4 para o padrão de venação para ambas espécies. As folhas são dorsiventrais, hipoestomáticas, com presença de células secretoras dispersas no mesofilo, feixes vasculares circundados inteira ou parcialmente por bainha esclerenquimática no limbo foliar, nervura central e pecíolo e, comumente, com tricomas em ambas faces. Apresentam epiderme com células de parede anticlinal em vista frontal curvada a reta em ambas as faces e eventualmente ondulada na face abaxial. Aréolas imperfeitas foram frequentes e vênulas dendríticas ocorrem para a maioria dos espécimes. As variações desses caracteres ocorreram entre as espécies, nos espécimes e na mesma amostra, sendo frequentemente encontradas para outras espécies da família. A importância taxonômica dos dados foliares necessita ser corroborada com outros estudos que englobem as demais espécies do Grupo Ocotea pulchella e outras espécies do gênero. Esses resultados apontam para a importância da análise de uma ampla amostragem de folhas em estudos que avaliem características relevantes para a delimitação taxonômica específica ou interespecífica.
Anatomical characterization of species of the genus Ocotea Aubl. (Lauraceae)
Keywords: Intraspecific variation; Stomata; Leaf anatomy; Laurales; Variação intraespecífica; Estômato; Anatomia foliar